Acute Posterior Ocular Toxoplasmosis: An Optical Coherence Tomography Angiography and Dye Angiography Study. (3rd April 2022) - Zicarelli, Federico; Pichi, Francesco; Parrulli, Salvatore; Oldani, Marta; Mapelli, Chiara; Riva, Agostino; Agarwal, Aniruddha; Viola, Francesco; Staurenghi, Giovanni; Invernizzi, Alessandro
ABSTRACT: Purpose: To compare Indocyanine Green (ICGA) and fundus fluorescein angiography (FFA) with Optical Coherence Tomography Angiography (OCTA) findings in toxoplasmic chorioretinitis (TCR). Methods: Patients affected by active TCR were included. FFA, ICGA, and OCTA images were analyzed and lesions were compared between different modalities. Satellite dark dots (SDD) were compared between modalities. Results: Fifteen patients were enrolled. The mean lesion area was similar between fundus photography (FP), FFA, and OCTA-Retina. The mean lesion area was similar between ICGA and OCTA-Choroid slab. ICGA and OCTA-Choroid showed a larger extension of the lesion compared to FP, FFA, and OCTA-Retina ( p = .01, 0.0001, and 0.0002 for ICG angiography and p = .03, 0.008, and 0.0002 for OCTA-Choroid, respectively). On OCTA B-scans, the retinal flow defects were smaller than the underlying choroidal non-perfusion. The number of SDD was similar between ICGA and OCTA. Conclusions: OCTA is a reliable method to assess retinal and choroidal involvement in TCR. OCTA confirmed a wider involvement of the choroid than the retina.